Managing Digital Fundraising of Dompet Dhuafa During Covid-19 Pandemic (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
Covid-19 pandemic demands zakah institutions to avoid physical contact activities, and outlet openings in public places. A marketing communication strategy is needed to make humanitarian mission and empowerment as zakah institutions’ core products synergize to resolve pandemic social impacts. Dompet Dhuafa, as a zakah institution, has developed fundraising digitalization to deal with the Covid-19 pandemic. This study describes fundraising digitalization as Dompet Dhuafa’s marketing communication strategy during the pandemic. Using a qualitative descriptive approach, it explores Dompet Dhuafa’s marketing communication strategy by literature study. Data are from Dompet Dhuafa’s website, Facebook, Instagram, Twitter, YouTube, relevant research journals, and articles. In building effective marketing communications, a marketer must consider designing a message, selecting message media, and choosing message sources. The results indicate that Dompet Dhuafa designs a message in each shared content to motivate people to pay zakah and ask for goodness. The message format is adjusted to message media in headlines, text, colors, and shapes. The message conclusion is generally conveyed in clear and strong arguments. Message media used are in digital-based personal and non-personal communication channels. Message sources are selected based on the conveyed messages.